1999
DOI: 10.1139/x99-116
|View full text |Cite
|
Sign up to set email alerts
|

An efficient Biolistic® transformation protocol for Picea abies embryogenic tissue and regeneration of transgenic plants

Abstract: An efficient Biolistic® transformation technology was developed to stably transform Picea abies (L.) Karst. Several embryogenic tissue lines were tested for proliferation on standard embryogenesis media. Transient transformation studies with these lines were performed to optimize the parameters for genetic transformation. Selection conditions for transgenic tissue based on the nptII resistance gene in combination with the antibiotic geneticin were defined such that only transgenic P. abies lines were able to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 26 publications
0
43
0
1
Order By: Relevance
“…the biolistic and Agrobacterium-mediated procedures. To date, only Picea abies was reported to be genetically modified using both methods [48,49]. In the family Pinaceae, the main group of gymnosperms subjected to transformation attempt [2], pine seemed generally more difficult to transform than spruce [16,43,48] or larch (reviewed in [35]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the biolistic and Agrobacterium-mediated procedures. To date, only Picea abies was reported to be genetically modified using both methods [48,49]. In the family Pinaceae, the main group of gymnosperms subjected to transformation attempt [2], pine seemed generally more difficult to transform than spruce [16,43,48] or larch (reviewed in [35]).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only Picea abies was reported to be genetically modified using both methods [48,49]. In the family Pinaceae, the main group of gymnosperms subjected to transformation attempt [2], pine seemed generally more difficult to transform than spruce [16,43,48] or larch (reviewed in [35]). Transient expression could be obtained in P. taeda, P. banksiana, P. contorta, P. sylvestris and P. palustris [12,30,49], but only two recent studies reported on stable transformation of ESM with regeneration of transgenic plants, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient expression was observed in electroporated protoplasts of loblolly pine (Pinus taeda L.) [3], as well as black spruce (Picea mariana) [4] tissues transformed by particle bombardment. Transgenic plantlets have been achieved in Norway spruce (Picea abies) [5], white spruce (Picea glauca) [6], black spruce (Picea mariana) [1], and radiata pine (Pinus radiata) [7] via microprojectile bombardment.…”
Section: Introductionmentioning
confidence: 99%
“…plants at an age of 8 to 10 months over-expressing the SPI1 spruce defensin protein displayed reduced fungal growth in the sapwood after inoculation with H. annosum [44]. Also, SPI1 spruce defensin that was expressed in tobacco permitted less growth of the bacterial pathogen Erwinia carotovora (Jones) Bergey et al [45], suggesting that SPI1 increases resistance in both homologous and heterologous systems. Furthermore, poplar trees transformed with a gene encoding synthetic peptide D4E1 were found to be resistant to bacterial pathogens Agrobacterium tumefaciens and Xanthomonas populi (Ridé) van den Mooter & Swings but not to the fungal pathogen Hypoxylon mammatum (Wahlenb.)…”
Section: Discussionmentioning
confidence: 99%